Inventory management: Multi-criteria ABC based on AHP in the warehouse of a metalworking company. - Leon Castro, Rocio; Vallejos Marquez, Maria; Caro Flores, Carlos; Idme Medina, Ishel; Pinto Valdiviezo, Angello (LACCEI, 2025)
Inventory management is essential to maintain competitiveness and productivity in the metalworking sector. This study analyzes the problems associated with inefficient inventory management in the warehouse of a company located in Villa El Salvador, Peru, specialized in metal structures and construction. Deficiencies include duplicate inputs, frequent losses, and lack of organization, which generate additional costs and affect operational efficiency.To address these problems, it is proposed to implement the multi-criteria ABC method based on the Analytical Hierarchy Process (AHP), a multi-criteria decision-making technique that classifies and prioritizes critical materials according to criteria such as unit cost, quantity of units, inventory cost, and shortage. The analysis includes the use of Ishikawa diagrams and simulations that identify the root causes of the problems and key areas for improvement.The results show that multi-criteria ABC classification significantly improves warehouse organization, record accuracy, and operational efficiency. A manageable and acceptable implementation cost for the company is estimated, with stages of training, organization, and implementation. This solution allows for more efficient management aligned with market demands, contributing to the optimization of logistics processes and increasing business competitiveness